Evolution of a major segmented normal fault during multiphase rifting: The origin of plan-view zigzag geometry. (May 2015) - Henstra, Gijs A.; Rotevatn, Atle; Gawthorpe, Robert L.; Ravnås, Rodmar
Abstract: This case study addresses fault reactivation and linkage between distinct extensional episodes with variable stretching direction. Using 2-D and 3-D seismic reﬂection data we demonstrate how the Vesterdjupet Fault Zone, one of the basin-bounding normal fault zones of the Lofoten margin (north Norway), evolved over c. 150 Myr as part of the North Atlantic rift. This fault zone is composed of NNE-SSW- and NE-SW-striking segments that exhibit a zigzag geometry. The structure formed during Late Jurassic and Early Cretaceous rifting from selective reactivation and linkage of Triassic faults. A rotation of the overall stress field has previously been invoked to have taken place between the Triassic and Jurassic rift episodes along the Lofoten margin. A comparison to recent physical analogue models of non-coaxial extension reveals that this suggested change in least principal stress for the Lofoten margin may best explain the zigzag-style linkage of the Triassic faults, although alternative models cannot be ruled out. This study underlines the prediction from physical models that the location and orientation of early phase normal faults can play a pivotal role in the evolution of subsequent faults systems in multi-rift systems. Highlights: In the Lofoten margin, the presence and geometry of early rift faults influenced the structural style of later rift episodes. During late stage rifting a single, through-going fault zone with zigzag geometry emerged. The multiphase evolution of the fault zone compares well with recent physical analogue models of non-coaxial extension. We discuss alternative models that can explain late phase zigzag-style linkage of early phase, parallel faults.